The practical guide to managing event venues - Berners, Philip (Abingdon, Oxon New York, NY Routledge, 2019)
"This is a short, accessible and practical guide to running venues which are in the business of hosting events. Using honest guidance peppered with the author's real-life situational anecdotes to contextualise the topics, the book is logically structured around the key stages of event management - pre-event, onsite and post-event. Topics covered include developing the client relationship, marketing, financial accountability, risk, interdepartmental communication, onsite procedures and post-event evaluation. This is a fundamental resource for all events management and hospitality students. It is also a book for anybody who manages a venue or is a venue event manager. The Practical Guide to Managing Event Venues makes the business of venue management appealing, understandable and achievable"-- Provided by publisher.
What is a venue? -- The hierarchy of event needs -- Hotels as venues for events -- Venue reputation -- History of a venue -- Testimonials -- Client portfolio -- Online reviews -- Events as a source of income -- Venue professionalism -- The need to meet expectations -- Venue culture change -- The one-person management structure -- The role of the venue -- Procuring external services -- Management of catering outlets / contribution from Jennifer Kaye -- Marketing, winning business & retaining clients -- Budgeting events / contribution from Adrian Martin -- Guests and venues -- Enquiry handling -- Show-round procedure -- Confirmation & contract procedure -- Lead-in procedure -- Client file procedure -- Client relationship procedures -- Event schedule/Function sheet -- Operational procedures -- Get-in & set-up procedure -- Rehearsal procedure -- Opening to closing procedures -- De-rig procedure -- Post-event procedures -- Case studies.
Includes bibliographical references and index.
Keywords: Special events -- Management; Special events -- Planning